Methylation status of hypothalamic Mkrn3 promoter across puberty - Fanis, Pavlos; Morrou, Maria; Tomazou, Marios; Michailidou, Kyriaki; Spyrou, George M.; Toumba, Meropi; Skordis, Nicos; Neocleous, Vassos; Phylactou, Leonidas A. (Frontiers in Endocrinology, 2023)
Makorin RING finger protein 3 (MKRN3) is an important factor located on chromosome 15 in the imprinting region associated with Prader-Willi syndrome. Imprinted MKRN3 is expressed in hypothalamic regions essential for the onset of puberty and mutations in the gene have been found in patients with central precocious puberty. The pubertal process is largely controlled by epigenetic mechanisms that include, among other things, DNA methylation at CpG dinucleotides of puberty-related genes. In the present study, we investigated the methylation status of the Mkrn3 promoter in the hypothalamus of the female mouse before, during and after puberty. Initially, we mapped the 32 CpG dinucleotides in the promoter, the 5’UTR and the first 50 nucleotides of the coding region of the Mkrn3 gene. Moreover, we identified a short CpG island region (CpG islet) located within the promoter. Methylation analysis using bisulfite sequencing revealed that CpG dinucleotides were methylated regardless of developmental stage, with the lowest levels of methylation being found within the CpG islet region. In addition, the CpG islet region showed significantly lower methylation levels at the pre-pubertal stage when compared with the pubertal or post-pubertal stage. Finally, in silico analysis of transcription factor binding sites on the Mkrn3 CpG islet identified the recruitment of 29 transcriptional regulators of which 14 were transcriptional repressors. Our findings demonstrate the characterization and differential methylation of the CpG dinucleotides located in the Mkrn3 promoter that could influence the transcriptional activity in pre-pubertal compared to pubertal or post-pubertal period. Further studies are needed to clarify the possible mechanisms and effects of differential methylation of the Mkrn3 promoter.